PENGARUH EXPERIENTIAL VALUE DAN SATISFACTION PENGUNJUNG FESTIVAL MAKANAN TERHADAP LOYALTY DI PASAR MALAM TJAP TOENDJOENGAN SURABAYA - Amanda Elisia Ardine; Siti Rahayu; Erna Andajani (CALYPTRA, 2018)
The purpose of this research is to determine and analyze the influence of Experiential ValueandSatisfaction of food festival visitors to Loyalty at Pasar Malam Tjap Toendjoengan Surabaya. The research uses the quantitative approach and the design of this research is causal. Variabel used un this research are Goal-Oriented Attendees, Experientially-Oriented Attendees, Experiential Value, Satisfaction, and Loyalty. Data analysis technique is Structural Equation Modelling(SEM) using SPSS 16.0 for windows and AMOS version 24. This study used a sample of respondents who have visited Pasar Malam Tjap Toendjoengan Surabaya. The number of samples used in this study were 200 respondents. The results of this study indicate the influence of Experiential Value of food festival visitors to Satisfaction and Loyalty at Pasar Malam Tjap Toendjoengan Surabaya.